Acute anemia of the infant due to subdural hematoma - Benedek, Pedro (Cirugía del Uruguay, 1974)
One of the author's patients presented a rare lesional association of acute anaemia caused by subdural hematoma. In such cases it is imperative to suspect, diagnose and rapidly operate tlie intracranial hematoma. Circulatory decompensation should not be attributed to an abdominal or thoracic lesion when it is a case of clear encephalo-cranail traumatism